On the need to improve state support for small and medium-sized enterprises as a factor in increasing the entrepreneurial activity of the small business - K. L. Neopulo (Путеводитель предпринимателя, 2020)
The paper considers and justifies the need to change the measures of state support for small and medium-sized businesses in order to increase the business activity index. The author analyzes the current state of small and medium-sized businesses, their contribution to GDP, considers measures of state support for small and medium-sized enterprises and their compliance with the principles of the development strategy. Perspective directions and approaches for improving the system of state support for small and medium-sized businesses that affect the growth of entrepreneurial activity in the Russian Federation are reflected.